1976
DOI: 10.1901/jeab.1976.25-279
|View full text |Cite
|
Sign up to set email alerts
|

FACILITATION OF HUMAN TOBACCO SELF‐ADMINISTRATION BY ETHANOL: A BEHAVIORAL ANALYSIS1

Abstract: T'he effect of ethaniol oin the cigarette smoking of alcoholic subjects was studied in a resi(leintial laboratory. Durinlg daily 6-hr sessions, cigarettes were obtained either by request to the ward staff or by operation of a lever (fixed-ratio 5 or 10). In a mixed sequence across (lays, sessions involved inigestion of either vehicle (orange juice) alonie or vehicle plus ethaniol (133.7 g). Dtirinig ethanol sessions, the rate of cigarette smoking increased from 26%y, to 117% of vehicle levels. A series of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
2

Year Published

1995
1995
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(93 citation statements)
references
References 16 publications
5
86
0
2
Order By: Relevance
“…The current study also demonstrated that once subjects decided to 'give in' and smoke, they smoked more cigarettes if they had consumed alcohol, supporting other human laboratory findings that alcohol increases smoking behavior (Griffiths et al, 1976;Mintz et al, 1985;Mitchell et al, 1995). In contrast to our results, Rose et al (2004) did not demonstrate any effect of alcohol on the number of cigarettes smoked.…”
Section: Discussionsupporting
confidence: 84%
“…The current study also demonstrated that once subjects decided to 'give in' and smoke, they smoked more cigarettes if they had consumed alcohol, supporting other human laboratory findings that alcohol increases smoking behavior (Griffiths et al, 1976;Mintz et al, 1985;Mitchell et al, 1995). In contrast to our results, Rose et al (2004) did not demonstrate any effect of alcohol on the number of cigarettes smoked.…”
Section: Discussionsupporting
confidence: 84%
“…Soon thereafter, the study of drug self-administration via operant responding was initiated in human research volunteers (Mendelson and Mello, 1966). One of the simplest operant schedules is the fixed-ratio (FR) schedule, in which participants make a fixed number of responses in order to obtain drug (e.g., Griffiths et al, 1976). For example, after every 200 responses on a manipulandum, participants receive a fixed amount of drug (FR200).…”
Section: Non-verbal Operant Proceduresmentioning
confidence: 99%
“…Epstein and Jennings (1986), demonstrated that alcohol, like coffee, can set t e occasion for increased smoking. Griffiths, Bigelow, and Liebson (1976), looked at the effect of alcohol (ethanol) on the cigarette smoking of alcoholic subjects. In this study, cigarettes were obtained either by request or by operation of a lever (FR 5 or 10) during daily 6 hour sessions.…”
Section: Application Of Behavioral Economicsmentioning
confidence: 99%